2016
DOI: 10.1007/s11010-016-2746-6
|View full text |Cite
|
Sign up to set email alerts
|

Valosin-containing protein (VCP) promotes the growth, invasion, and metastasis of colorectal cancer through activation of STAT3 signaling

Abstract: Valosin-containing protein (VCP) was previously shown to exhibit high expression in colorectal cancer (CRC) tissues as compared with that in normal tissues; however, the role of VCP in human CRC cells has remained to be elucidated. Two colorectal cancer cell lines HCT116 and RKO were used in the experiment. We introduced lentiviral constructs expressing VCP to infect RKO cells and lenti-shRNA targeting VCP into HCT116 cells, respectively. Cell proliferation, invasion, apoptosis, and cell cycle arrest were subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
1
24
0
2
Order By: Relevance
“…RNAi mediated depletion of VCP induces the apoptotic cell death in Hela cells (Wojcik, Yano, & DeMartino, ). Higher expression VCP has a positive correlation with the proliferation and metastasis of colorectal cancer (Fu et al, ). In our study, downregulation or inhibition of VCP diminishes cell growth and anchorage independent growth of PCa cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAi mediated depletion of VCP induces the apoptotic cell death in Hela cells (Wojcik, Yano, & DeMartino, ). Higher expression VCP has a positive correlation with the proliferation and metastasis of colorectal cancer (Fu et al, ). In our study, downregulation or inhibition of VCP diminishes cell growth and anchorage independent growth of PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the altered proteins, valosin‐containing protein (VCP) is a member of the AAA ATPases was identified as overexpressed protein which formed a central node in protein network analysis. Elevated VCP expression show positive correlation with progression, metastatic potential of Non‐small cell lung cancer (NSCLC), Ovarian, Colorectal cancer, and Osteosarcoma (Bastola, Neums, Schoenen, & Chien, ; Fu et al, ; Long, Zhang, Liu, Huang, & Luo, ; Valle et al, ). Furthermore, it has been reported that elevated VCP expression would lead to the poor prognosis of PCa (Tsujimoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knockdown of Bap31 arrests the cell cycle at the G0/G1 phase Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry [34]. The protein levels of cyclin D1, cyclin E, CDK2, CDK4, Ki-67 and PCNA were decreased in shRNA-VCP-transfected cells [26]. Moreover, ER stress marker levels were increased in Bap31 knockout mice after tunicamycin injection compared with those in control mice [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bcl2, which is an important anti-apoptosis molecule, regulates the cell cycle by enhancing G0 and delaying the G0 to S transition. Its noted that the knockdown of VCP downregulates the protein levels of Bcl2 [26]. VCP regulates the expression levels of Bap31 maybe via the Bcl2 mediated cell cycle.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%